Strategi Perwujudan Pembelajaran Humanis di Madrasah I’dadiyah Salafiyah Syafi’iyah Sukorejo - Sabil, Afif (STAI Nurul Huda Kapongan Situbondo, 2021)
Learning that values students as free individuals, aware of their potential, communicative, critical, fun and full of humanist values is important to exist. This paper aims to determine the strategy of Madrasah I'dadiyah in the realization of humanist learning. The research method used is qualitative with the type of case study, the data collection techniques are observation and interviews. The strategy of Madrasah I'dadiyah in the realization of humanist learning is through four stages. First, determine the direction and goals to be achieved, then choose the most appropriate way to realize the goals. Second, determine the approach in the teaching and learning process. Third, choose the method that best suits the objectives and approaches that have been chosen. Fourth, determine the standards that will be used as guidelines for the next learning process.